2023
DOI: 10.1186/s13000-023-01373-1
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic small round cell tumor of the liver: diagnosing a rare case on liver biopsy

Abstract: Desmoplastic small round-cell tumors (DSRCT) frequently develop in the retroperitoneum, pelvis, omentum, and mesentery. Here, we present an unusual case of primary DSRCT in the liver. The patient was an 11-year-old boy with multiple solid masses in the liver parenchyma. The tumor in the needle biopsy had a histology revealing a small round cell morphology and desmoplasia. It shows the immunohistochemical features of DSRCT and documentation of EWSR1-WT1 fusion.A potential diagnostic pitfall is exerted when eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…DSRCTs were identified and characterized by Gerald and Rosai in 1989 [9]. The mean age of diagnosis is approximately between 19 and 22 years, ranging from 6 to 49 years, with a male predominance of 75% [5,10]. In accordance, the present case was a male in his forties.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…DSRCTs were identified and characterized by Gerald and Rosai in 1989 [9]. The mean age of diagnosis is approximately between 19 and 22 years, ranging from 6 to 49 years, with a male predominance of 75% [5,10]. In accordance, the present case was a male in his forties.…”
Section: Discussionsupporting
confidence: 80%
“…However, Baydar et al reported 11 cases of primary renal DSRCT, of which seven were females and presented with gross haematuria and abdominal pain [3]. The abdominal cavity is the most common site for tumor development [5]. This rare malignant soft tissue tumor is associated with a poor prognosis and extreme aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is extremely rare in clinical practice, with few reports in the literature, a high misdiagnosis rate, and poor prognosis ( 18 ). Interestingly, recent reports have mainly focused on cases of Ewing sarcoma of the colon/PNET combined with liver metastasis, with an overall cure rate of only 20% for metastatic Ewing sarcoma ( 25 , 26 ). It is noteworthy that the median survival time for small round cell undifferentiated sarcoma is less than 2 years ( 19 , 27 ), and the 5-year survival rate for 57 patients with CIC rearrangement sarcoma was 43%, lower than that of Ewing sarcoma ( 28 ).…”
Section: Discussionmentioning
confidence: 99%